Scale heterogeneity in recreationists' decision making: Evidence from a site choice model of sport fishing. (June 2017) - Melstrom, Richard T.; Jayasekera, Deshamithra H.; Boyer, Tracy A.; Jager, Corey
Abstract: Recreation managers and planners recognize the importance of individual preferences and analysts have responded by incorporating individual and group-level heterogeneity in models of recreation behavior. We present a site choice model of recreational fishing that incorporates unobserved heterogeneity through a scale effect. By testing for scale heterogeneity, the model more accurately measures variation in site preferences compared with a conditional logit model, and demonstrates that site quality can affect fishing behavior unevenly across individuals. This result has important implications when using the model to predict fishing behavior and to value site quality and site access. We used the results to simulate the welfare impacts of several hypothetical improvements in fish abundance and find that ignoring scale heterogeneity can lead to inflated economic benefit estimates. Management implications: The information in this study can be used by fisheries managers to economically substantiate and motivate actions to enhance the benefits of recreational fishing. The analysis demonstrates that diversity of preferences means some anglers choose fishing sites based on information about catch and accessibility, while others care less about these characteristics. Nevertheless, in general, we find that anglers in the U.S. southwest value increases in bass and walleye abundance as well as state programs to improve public fishing access.